2021
DOI: 10.3390/molecules26247477
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Pectin-Murta (Ugni molinae T.) Seed Extract Films Reinforced with Chitin Fibers

Abstract: This study investigated the biocomposite pectin films enriched with murta (Ugni molinae T.) seed polyphenolic extract and reinforced by chitin nanofiber. The structural, morphological, mechanical, barrier, colorimetric, and antioxidant activity of films were evaluated. The obtained data clearly demonstrated that the addition of murta seed extract and the high load of chitin nanofibers (50%) provided more cohesive and dense morphology of films and improved the mechanical resistance and water vapor barrier in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
1
1
1
Order By: Relevance
“…This increase in chain movement was also reflected in the results of the mechanical properties (Figure 5). The ability to reduce water vapor permeation presented by the materials obtained in this study was better than that reported for starch, pectin, and chitosan-zein films [16,37,38].…”
Section: Gas Permeabilitycontrasting
confidence: 80%
“…This increase in chain movement was also reflected in the results of the mechanical properties (Figure 5). The ability to reduce water vapor permeation presented by the materials obtained in this study was better than that reported for starch, pectin, and chitosan-zein films [16,37,38].…”
Section: Gas Permeabilitycontrasting
confidence: 80%
“…22 However, the hydrogen bonding appeared to decrease after the GTE content reached 2%. Similar findings were reported in studies done by Cabrera-Barjas et al 23 This could be explained by the aggregation of the GTE when it exceeded 2% and the saturation of the binding sites, which resulted in the limitation of hydrogen bond formation between the GTE and the film polymeric matrix. 24 Similar results were reported by Biao et al when they tested the effect of different concentrations of tea polyphenols added to alginate polymeric films.…”
Section: F I G U R E 2 Attenuated Total Reflectionsupporting
confidence: 89%
“…[71][72][73][74] On the other hand, CHNCs can improve the antibacterial activity of enzymes like lysozyme by acting as immobilization platforms, 75 and the antioxidant activity of immobilized phlorotannins. 76 Also, nanocomposites films based on chitosan, 77 carrageenan, 78 carboxymethyl cellulose, 79 methylcellulose, 80 cellulose nanofibers, 39,81 pectin, 82 nanolignin, 83 polyl-actic acid, 38,84 highly porous and spongy monolith cryogel of polyvinyl alcohol 85 and molybdenum disulfide quantum dots, 86 have been developed. Regarding antifungal activity, films have been developed using CHNFs alone, 87 in combination with chitosan 88 or by incubation in sodium hypochlorite solution.…”
Section: Antibacterial Agentsmentioning
confidence: 99%